2017
DOI: 10.1038/s41598-017-14739-5
|View full text |Cite
|
Sign up to set email alerts
|

Application of Lysine-specific Labeling to Detect Transient Interactions Present During Human Lysozyme Amyloid Fibril Formation

Abstract: Populating transient and partially unfolded species is a crucial step in the formation and accumulation of amyloid fibrils formed from pathogenic variants of human lysozyme linked with a rare but fatal hereditary systemic amyloidosis. The partially unfolded species possess an unstructured β-domain and C-helix with the rest of the α-domain remaining native-like. Here we use paramagnetic relaxation enhancement (PRE) measured by NMR spectroscopy to study the transient intermolecular interactions between such inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…We found that SAP can counteract the toxicity induced by the expression of F57I by promoting the formation of alternative morphologies of aggregated lysozyme with more amyloidogenic characteristics. We tested the effect of SAP on in vitro lysozyme fibril formation, using the well-studied I59T lysozyme system [21,22] and confirmed that the presence of SAP promoted enhanced ThT Competing interests: The authors have declared that no competing interests exist.…”
Section: Introductionmentioning
confidence: 73%
“…We found that SAP can counteract the toxicity induced by the expression of F57I by promoting the formation of alternative morphologies of aggregated lysozyme with more amyloidogenic characteristics. We tested the effect of SAP on in vitro lysozyme fibril formation, using the well-studied I59T lysozyme system [21,22] and confirmed that the presence of SAP promoted enhanced ThT Competing interests: The authors have declared that no competing interests exist.…”
Section: Introductionmentioning
confidence: 73%
“…In these intermediates, the β-domain is largely unfolded and able to establish inter-molecular contacts that drive the aggregation of the protein. [59] The aggregation rate of human lysozyme largely correlates with the destabilisation of the native state of the protein and the formation of intermediates. [60,61] In vivo, human lysozyme misfolding occurs as a consequence of pathological mutations.…”
Section: Human Lysozyme: the Model Par Excellence Of Protein Misfoldingmentioning
confidence: 99%
“…We chose to study lysozyme and insulin, two clinically relevant, well-characterized proteins which crystallize readily and whose self-assembly kinetics have been explored as a function of protein structure. 14 In this study, we evaluate the impact of these bioconjugates on protein crystallization and examine how they affect protein crystallization kinetics.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Indeed, proteins naturally self-assemble on the nano- and microscale to form highly ordered structures such as crystals, fibrils, or amorphous aggregates . Previous work has shown that intermolecular interactions drive protein aggregation and fibrillation. , In addition, nanofibril structures can even be designed by modifying specific bonds or amino acid residues . A surface of highly ordered proteins can drive the protein crystal nucleation in the same way that seeding a solution with small protein crystals (often practiced in large-scale crystallization) can enhance protein crystal growth.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation